A Dual Carbon‐Based Potassium Dual Ion Battery with Robust Comprehensive Performance. Issue 31 (3rd July 2018) - Zhu, Jiaojiao; Li, Yali; Yang, Bingjun; Liu, Lingyang; Li, Junshuai; Yan, Xingbin; He, Deyan
Abstract: Dual carbon‐based potassium dual ion batteries (K‐DCBs) have recently attracted ever‐increasing attention owing to the potential advantages of high performance‐to‐cost ratio, good safety, and environmental friendliness. However, the reported K‐DCBs still cannot simultaneously meet the requirements of high capacity, long cycling stability, and low cost, which are necessary for practical applications. In this study, a K‐DCB with good comprehensive performance including capacity, cycling stability, medium discharge voltage, and energy density is developed by introducing the optimal cathode and anode materials, i.e., KS6 and natural graphite, respectively. An initial capacity of ≈54.6 mAh g −1 and 92.5% capacity retention after 400 cycles can be delivered in a wide voltage window of 2.4–5.4 V at the current density of 100 mA g −1 . A high medium discharge voltage around 4.2 V and an energy density up to 158.3 Wh kg −1 are meanwhile delivered by the K‐DCB. In addition, the working mechanism of the devices is understood in detail. It is believed that valuable contributions to the electrochemical performance improvement of the related devices toward practical applications can be provided by this study. Abstract : The dual carbon‐based potassium dual ion battery exhibits good comprehensive performance of capacity, cycling stability, medium discharge voltage, and energy density. It can light up two‐series‐connected light emitting diodes (one is a red LED and the other is a blue LED).